What Side Are You On? - Wilson, Michael Steven; Lucero, José Antonio (The University of North Carolina Press, 2025)
Renowned human rights activist Michael “Mike” Wilson has borne witness to the profound human costs of poverty, racism, border policing, and the legacies of colonialism. From a childhood in the mining town of Ajo, Arizona, Wilson’s life journey led him to US military service in Central America, seminary education, and religious and human rights activism against the abuses of US immigration policies. With increased militarization of the US-Mexico border, migration across the Tohono O’odham Nation surged, as did migrant deaths and violent encounters between tribal citizens and US Border Patrol agents. When Wilson’s religious and ethical commitments led him to set up water stations for migrants on the Nation’s lands, it brought him into conflict not only with the US government but also with his own tribal and religious communities. This richly textured and collaboratively written memoir brings Wilson’s experiences to life. Joining Wilson as coauthor, José Antonio Lucero adds political and historical context to Wilson’s personal narrative. Together they offer a highly original portrait of an O’odham life across borders that sheds light on the struggles and resilience of Native peoples across the Americas.